International Students’ Perceived Language Competence, Domestic Student Support, and Psychological Well-Being at a U.S. University - Luo, Zhengda; Wu, Siyu; Fang, Xuanyu; Brunsting, Nelson (Journal of International Students, 2019)
To increase knowledge of international students’ psychological well-being at U.S. universities, we examined the degree to which demographic factors, perceived language competence, and domestic student social support were associated with Ryff’s (1989a, 1989b) six aspects of psychological well-being. Participants (n = 216) were undergraduate and graduate students from one mid-sized private university in the Southeast. Analyses revealed differential psychological well-being scores based on demographics. Perceived language competence and domestic student social support were associated positively with multiple aspects of psychological well-being. The novel findings of this case study provide initial evidence of a potentially useful new approach toward international student adjustment and well-being. The authors provide initial recommendations for researchers, practitioners, and international students.